Secondary Victimization and Criminal Liability of Crime Victims in the Sleman Snatching Case: A Human Rights Criminology Perspective - Hajar Salamah Salsabila Hariz; M. Rizal Qosim; Muchlis Fathulloh; Hariyanto Hariyanto (Universitas Lampung, 2026)
Snatching is a street crime that threatens personal security and prompt spontaneous responses from victims or their family members when formal protection is unavailable or perceived as inadequate. This article examines secondary victimization and criminal liability in the Sleman snatching case, in which the victim's husband pursued the alleged offender after his wife was robbed and later became subject to legal scrutiny following the alleged offender's death during the pursuit. This study employs normative legal research using statutory, conceptual, case, and human rights criminology approaches. The analysis demonstrates that the case cannot be reduced to a simple narrative of victim criminalization. Instead, it highlights the interaction between victim-offender overlap, lawful defense, causation, proportionality, and human rights protection. Criminal liability in cases involving spontaneous victim responses should be assessed by examining necessity, immediacy, proportionality, causation, culpability, and due process. The article concludes by proposing a human rights-based framework for assessing criminal liability that prevents secondary victimization while preserving accountability for serious legal consequences.